(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Scabies is an important parasitic skin disease that continues to persist all over the world. The current study was designed to asses some immunological parameters that may be related with scabies disease Blood samples were collected from 60 patients (30 first infestation,30 re-infestation) with ordinary scabies and 30 healthy individuals as a control group to determine the total and differential WBCs count , in addition sera levels of some immunological parameters including, C3,IgE and Indoleamine 2,3 dioxygenase (IDO). The results revealed that a significant increase (P?0.05) in total and differential WBCs count of patients groups compared with healthy group , also the levels of immunoglobulin IgE and IDO showed a significant increase (P?0.05) in patients groups in comparison with healthy group . Concerning with complement components (C3) its levels observed a significant differences (P?0.05) between patients groups(first infestation and re infestation) , also between patients and healthy group .